Pengaruh Penambahan Prebiotik Dan Probiotik Dalam Pakan Terhadap Performa Pertumbuhan Ikan Budidaya : Studi Literatur - Andika Taufik Perdamaian Telaumbanua; Ratna Dewi Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Intensive fish farming faces challenges such as disease, low feed efficiency, and declining water quality. This article aims to examine the effect of adding prebiotics and probiotics to feed on the growth performance of farmed fish through a literature review of various scientific journals. The results of the review indicate that probiotics improve gut microbiota balance, digestive enzyme activity, growth, and feed efficiency, while prebiotics support the growth of beneficial bacteria and boost the fish’s immune system. The combination of both (synbiotics) provides better results than using them separately. Thus, the addition of prebiotics and probiotics has the potential to be an effective and environmentally friendly nutritional strategy to improve the growth, health, and productivity of farmed fish.